Social support or biosocial support?: a genetically informative analysis of social support and its relation to self-control - Beaver, Kevin M. (Criminal justice and behavior, 2014)
There is growing interest in examining whether the findings generated from biosocial studies of crime can be integrated into existing criminological theories. To this point, however, not much empirical research has focused on this possibility. The current study addresses this gap in the literature by examining the nexus between biosocial criminology and the social support perspective as it relates to levels of self-control. To do so, a sample of twin pairs from the National Longitudinal Study of Adolescent Health (Add Health) was analyzed using quantitative genetic analyses. The analyses revealed three key findings. First, genetic factors account for about 50% of the variance in measures of social support. Second, the covariance between social support and self-control is largely due to a common genetic pathway. Third, even after holding genetic influences constant, social support has a significant effect on levels of self-control.